2008
DOI: 10.1111/j.1349-7006.2008.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Translational microarray systems for outcome prediction of hepatocellular carcinoma

Abstract: DNA microarray technology has revolutionized our understanding of the molecular basis of hepatocellular carcinoma (HCC), one of the most fatal human cancers with a high recurrence rate. Many researchers have used DNA microarray technology to reclassify HCC with respect to metastatic potential and to develop predictors for the outcome of HCC. However, developed predictors have reached the level only of small retrospective studies, and their current status is far from that required for clinical use. This is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…The predictive accuracy of predictors ranges from 73 to 97%. No association was observed between the predictive accuracy and background factors, such as the number of genes used in predictors or test samples, publication year, and the array type [22]. Budhu et al [21] used the noncancerous liver tissue specimens to predict the early recurrence of HCC.…”
Section: Molecular Prediction Of Early and Late Recurrence Of Hccmentioning
confidence: 98%
See 2 more Smart Citations
“…The predictive accuracy of predictors ranges from 73 to 97%. No association was observed between the predictive accuracy and background factors, such as the number of genes used in predictors or test samples, publication year, and the array type [22]. Budhu et al [21] used the noncancerous liver tissue specimens to predict the early recurrence of HCC.…”
Section: Molecular Prediction Of Early and Late Recurrence Of Hccmentioning
confidence: 98%
“…In another study [23], late recurrence was simply defined as tumor recurrence occurring more than 2 years after surgery. However, HCC recurrence due to intrahepatic metastasis can appear even 3 years after surgery, and intrahepatic recurrence due to de novo HCC can appear within 1 year after surgery [22,32]. A follow-up period after surgery is very important to determine whether patients have the late recurrence of HCC.…”
Section: Molecular Prediction Of Late Recurrence Of Hcc Using Nontumomentioning
confidence: 99%
See 1 more Smart Citation
“…Lau et al reported on the first study of an expression array for HCC in 2000 (37). Subsequently, many studies were performed to discover novel candidates of tumor suppressor genes in HCC using expression array technology (38)(39)(40). Moreover, SNP chip array analysis, which now enables us to simultaneously detect a large number of DNA polymorphic loci in a simple way, was further developed for genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Such prediction models for HCC metastasis are expected to impact clinical practice since an appropriate therapeutic regime can be applied to patients with high-risk of recurrence (Budhu et al 2005b). Accordingly, specific gene expression signatures in tumor and surrounding nontumor tissues have been identified, and prediction models have been developed to predict vascular invasion, early intrahepatic recurrence, and metastasis (Iizuka et al 2008;Budhu et al 2005a;Iizuka et al 2008).…”
Section: Gene Signatures For Recurrence and Metastasismentioning
confidence: 99%